Tourism event economic impact & customer experience study : Pesta Benak 2011 / Nuraini Putit … [et al.]. - Putit, Nuraini; Atlas, Ranee; Atan, Patrick; Jugah, Ivy; Jingut, Robert (2011)
The study of Economic Impact and Visitor's Experience on the Tidal Bore Festival or Pesta Benak 2011 is to find out what are the contributions of this event towards the local community in Sri Aman and nearby areas. The study was conducted from 1st to 4th July 2011 at the festival location in Sri Aman Waterfront (Batang Lupar).